Therapeutic advances in overcoming intrauterine growth restriction induced metabolic syndrome - Mutamba, Alpha Kalonda; He, Xiaori; Wang, Tao (Frontiers in Pediatrics, 2023)
Intrauterine growth restriction (IUGR) remains a great public health challenge as it affects neonatal survival and influences their normal biological development and metabolism. Several clinical researches have revealed the occurrence of metabolic syndrome, such as insulin resistance, obesity, type 2 diabetes mellitus, oxidative stress, dyslipidemia, as direct results of IUGR. Therefore, it is essential to understand its underlying mechanism, impact and develop effective therapies. The purpose of this work is to review the current knowledge on IUGR induced metabolic syndrome and relevant therapies. Here in, we elaborate on the characteristics and causes of IUGR by pointing out recent research findings. Furthermore, we discuss the impact of IUGR on different organs of the body, followed by preclinical studies on IUGR using suitable animal models. Additionally, various metabolic disorders with their genetic implications, such as insulin resistance, type 2 diabetes mellitus, dyslipidemia, obesity are detailed. Finally, the current therapeutic options used in the treatment of IUGR are summarized with some prospective therapies highlighted.